2012
DOI: 10.4049/jimmunol.1102466
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Characteristics of the Immunoglobulin VH Repertoire of Chickens in Comparison with Those of Humans, Mice, and Camelids

Abstract: Examination of 1269 unique naive chicken VH sequences showed that the majority of positions in the framework (FW) regions were maintained as germline, with high mutation rates observed in the CDRs. Many FW mutations could be clearly related to the modulation of CDR structure or the VH–VL interface. CDRs 1 and 2 of the VH exhibited frequent mutation in solvent-exposed positions, but conservation of common structural residues also found in human CDRs at the same positions. In comparison with humans and mice, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
99
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 70 publications
12
99
3
5
Order By: Relevance
“…A recent bioinformatic study has shown that the chicken V H domain repertoire is highly homologous to that of humans and mice in both the frameworks and CDR1 and CDR2 (32). In contrast, chickens use a much longer V H CDR3 repertoire and frequently stabilize these long binding loops by introducing non-canonical disulfide bonds (32).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent bioinformatic study has shown that the chicken V H domain repertoire is highly homologous to that of humans and mice in both the frameworks and CDR1 and CDR2 (32). In contrast, chickens use a much longer V H CDR3 repertoire and frequently stabilize these long binding loops by introducing non-canonical disulfide bonds (32).…”
Section: Discussionmentioning
confidence: 99%
“…S1. Each of these clones was found to have the high framework uniformity that is typical of chicken antibodies (32). They are highly divergent in their V H CDR3 sequences, however, with the exception of pT231/pS235_1 and pT231/ pS235_2, which have identical heavy chain sequences but exhibit promiscuity in light chain usage.…”
Section: Generation Of Chicken Antibodies Specific To Phosphorylatedmentioning
confidence: 99%
See 3 more Smart Citations